Hydrodynamic Characteristics of the Pusher, Tractor and Schottel Types of the Azipod Propulsion System - Gholami Hossein; Ghassemi Hassan; He Guanghua; Shamsi Reza (Polish Maritime Research)
The main purpose of this paper is to investigate the hydrodynamics performance of the three types (pusher, tractor and Schottel) of the azimuthing podded drive (AZIPOD) electric propulsion system. To evaluate the propulsive performance of the podded drive system, the Reynolds-Averaged Navier Stokes (RANS) solver is employed. KP-505 propeller as the research object, hydrodynamic open-water characteristics of this propeller was first calculated, and agreed well with test results. Then, numerical simulation of the thrust, torque and efficiency of the three types of the AZIPOD systems (Pusher, Tractor and Schottel) with KP-505 propeller at various yaw angles (from -30° to +30° with 15° increments) and different advance coefficients were compared. For the Schottel propulsion system, the effects of the number of propeller blades and the blade pitch-diameter ratio on performance are presented and discussed. Finally, the effect of sturt, support element and pod for pusher type on the pressure coefficient, thrust and torque of one blade and whole blades is investigated during one cycle.